ACHIEVEMENTS AND PROSPECTS IN THE DIAGNOSIS AND TREATMENT OF HEPATITIS, CURRENT PROBLEMS OF VIRAL ETIOLOGY OF HEPATITIS IN CHILDREN - Aripov A. N.; Aripov O. A.; Akhunjanova L. L.; Nabiev A. O.; Karimov Sh. B.; Muhammadjonov B. B.; Khamroev T. T. (Journals Park Publishing, 2022)
This paper summarizes, based on the experience of clinicians and scientists, viral, especially chronic viral hepatitis, a disease that is currently leading in frequency of occurrence and severe manifestations of complications, as well as causes of mortality. It describes the advantages and disadvantages, as well as the problems currently achieved in medicine for accurate, complete and timely diagnosis and treatment of the disease. The publication also spoke about the achievements achieved in our country in the field of diagnosis and treatment of viral hepatitis, as well as the research conducted in this area.
Keywords: Diagnosis of chronic hepatitis, treatment of chronic hepatitis cirrhosis of the liver, liver failure